Strengthening Women's Perspectives in General Elections by Political Parties - Pawestri, Aprilina; Wahyuliana, Ida (Law Research Review Quarterly, 2018)
Women's issues are not always present in the vision and mission the members of the legislative or presidential candidates and Vice President who carried out by political party in the elections, if one compared the economic issues and the law. As a result of the party system that is practised in the election, political party being the only vehicle that will bring this candidate as a Shaper and implementer of policies. As referred to in article 1 paragraph (1) of law No. 2 of year 2011 about the change of Act No. 2 of the year 2008 about political parties. Vision and mission delivered a little to much impact on the turn out of women at the time of the election venue. The question is not only 30% representation of women as members of the legistatif, but how the rights and protection of women, one example of the large number of violations of the rights of women. The country's present to satisfy the interests of its citizens. One of them is represented through the political parties, as part of which is inseparable with our national objectives in the preamble to The Constitution of the Republic of Indonesia in 1945 protect all the Nations and all the spilled blood of Indonesia.